THE PROBLEMS OF MODELING THE EVOLUTION OF THE DYNAMIC SYSTEM, INTERACTING WITH THE ENVIRONMENT - V. L. ZAKOVOROTNY; DINH TUNG PHAM (Advanced Engineering Research)
The article proposes a new method of modeling the evolutional system, which interacts with the environment. The cutting process or tribo-space, which are formed in the contact area of two conjugate mechanical subsystems, are considered as an environment. The features of the environment depend not on the coordinates of the state of the system, but on the trajectories. That is why the parameters of the environment are performed not as integral operators of the equations like Volter equation.